Stability and Strength Criteria for High Performance Steel Plates Under Egde Compression - Kıymaz, Güven (İstanbul Kültür Üniversitesi Yayınları, 2003)
A Study of imperfect plate panels under compression is presented with emphasis being given on the effect on plate strength of different material and initial imperfection characteristic of high strength steel plates, in comparisonto mild steel plates. Non-linear finite element analyses of imperfect plate panels were conducted over a practical range of plate slenderness. More realistic material behavior and residual stresses were adopted in modeling of high strength steel plate panels. Ultimate strength trends for mild steel and high strength steel plates over a wide range of plate slenderness were compared which led to a simple desing aquation that would account for the observed difference in non-dimensional plate strength of imperfect high strength steel plates.

Çalışma eksenel basınç altındaki kusurlu yumuşak çelik ve yüksek mukavemetli çelik panellerin değişik malzeme özellikleri ve ön kusur özellikleri göz önüne alınarak taşıma kapasitelerinin karşılaştırılması üzerinedir. Kusurlu paneller değişken narinlik aralığında non-lineer sonlu eleman metoduyla incelenmiştir. Yüksek mukavemetli çelik panellerin modellenmesinde gerçeğe yakın malzeme davranışı ve ön kusur özellikleri benimsenmiştir. Narinlik aralığında yumuşak çelik ve yüksek mukavemetli çelik panellerin taşıma kapasiteleri karşılaştırılmış, iki çelik grubu arasında gözlenen fark basit bir hesap formülü ile ifade edilmiştir.
Keywords: high performance steel; plate stability; plate imperfections; finite element analysis; yüksek performanslı çelik; plaka stabilite; plaka kusurlar; sonlu elemanlar analizi